2019
DOI: 10.3390/nu11051120
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides Rg5 and Rk1 Enriched Cultured Wild Ginseng Root Extract Bioconversion of Pediococcus pentosaceus HLJG0702: Effect on Scopolamine-Induced Memory Dysfunction in Mice

Abstract: Wild ginseng is known to contain additional physiologically and pharmacologically active substances than common ginseng. The utilization of this herb can be maximized by altering its composition via tissue culture generating adventitious roots. We enriched the content of specific ginsenosides and investigated their role in ameliorating memory impairment. Cultured wild ginseng root was subjected to extraction, steaming, and fermentation using Pediococcus pentosaceus HLJG0702 to enhance the levels of ginsenoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Even ginseng root-extracted P. pentosaceus HLJG0702 was found to be able to produce HLJG0701. HLJG0701 also significantly improved the concentration of the ginsenosides Rg5/Rk1 to inhibit acetylcholinesterase in scopolamine-induced memory dysfunction mice, which manifested as an improvement in brain function [ 138 ].…”
Section: Potential Special Ability Of P Pentosaceusmentioning
confidence: 99%
“…Even ginseng root-extracted P. pentosaceus HLJG0702 was found to be able to produce HLJG0701. HLJG0701 also significantly improved the concentration of the ginsenosides Rg5/Rk1 to inhibit acetylcholinesterase in scopolamine-induced memory dysfunction mice, which manifested as an improvement in brain function [ 138 ].…”
Section: Potential Special Ability Of P Pentosaceusmentioning
confidence: 99%
“…The anti‐acetylcholinesterase activity of steamed SLS was almost unchanged after steaming at 100°C for 4 h. The anti‐acetylcholinesterase activity of steamed SLS was gradually increased with the extension of steamed time at 120°C and 140°C, and reached the maximum after steaming at 140°C for 3 h. However, the anti‐acetylcholinesterase activity slightly decline when the steamed time achieved 4 h at 140°C. Previous research has suggested that ginsenosides Rk1 and Rg5 have a protective effect on neurodegenerative diseases (An et al, 2019; Kim et al, 2013). Therefore, the anti‐acetylcholinesterase activities of ginsenosides Rk1 and Rg5 were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-acetylcholinesterase activities of SLS and steamed SLS were assessed in vitro and summarized in (An et al, 2019;Kim et al, 2013). Therefore, the anti-acetylcholinesterase activities of ginsenosides Rk1 and Rg5 were assessed.…”
Section: In Vitro Anti-acetylcholinesterase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural growth rate of wild ginseng is very low, making it difficult to commercialize. Luckily, cultured wild ginseng roots produced by in vitro culture are known to have a similar genetic DNA to wild ginseng, with high saponin contents [ 50 , 51 ]. In this study, we optimized an adventitious root culture of ginseng using a bioreactor [ 52 ].…”
Section: Discussionmentioning
confidence: 99%